(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Chronic Obstructive Pulmonary Disease (COPD) and its exacerbation are a major cause of pulmonology OPD and emergency visits in Pakistan. The objective of this study was to measure the level of adherence to the GOLD (Global Initiative for Chronic Obstructive Lung Disease) strategy document in the management of patients with acute exacerbation of COPD, in Sahiwal Punjab Pakistan. Methodology: This retrospective cross-sectional study comprised 480 patients with acute exacerbation of COPD. It was conducted in the Pulmonology Department DHQ Teaching Hospital, Sahiwal. The treatment given to these patients was compared to treatment guidelines mentioned in the GOLD strategy document for management of acute exacerbation of COPD. Results: Out of total 480 patients, 408 (85%) were males. 312 (65%) patients belonged to age group 50-70 years. 100% Gold strategy treatment standards were not followed in any patient. Five out of ten management steps were followed in all cases. While remaining five steps were followed variably. Conclusion: Overall adherence to the AECOPD management standards set by GOLD strategy document was not good. Improved physician’s awareness of guidelines and better adherence to treatment standards can improve patient care and outcome.